Genetic study of Staphylococcus Aureus Isolates from Different Environmental Source - Ansejam Yaaqop Khadem; Abbas Abod Farhan; Khaleb Edres Ateea (Diyala Journal of Medicine, 2018)
Background: Bacteria Staphylococcus aureus are from nurses and serious task because of the ability to cause various types of injuries at different locations of the body, and that pathogenesis has nothing to do with their ability to produce many virulence factors.  Objective: To detection of virulence genes for Staphylococcus aureus isolates from different environmental source .